Early recurrence during the blanking period and left atrial reverse remodeling after catheter ablation for non-paroxysmal atrial fibrillation. (October 2020) - Oka, Takafumi; Koyama, Yasushi; Tanaka, Koji; Hirao, Yuko; Tanaka, Nobuaki; Okada, Masato; Yoshimoto, Issei; Kitagaki, Ryo; Okamura, Atsunori; Iwakura, Katsuomi; Sakata, Yasushi; Fujii, Kenshi; et al.
Abstract: Background: Early recurrence of atrial tachyarrhythmia (ERAT) during a 90-day blanking period (BP) often occurs after atrial fibrillation (AF) ablation. Left atrial reverse remodeling (LARR), which is the reduction in LA volume (LAV), also occurs during the BP. Both ERAT and LARR are associated with late recurrence (LR, greater than 90 days after ablation). We investigated the association between ERAT and LARR following non-paroxysmal AF (NPAF) ablation. Methods: We retrospectively reviewed 330 consecutive patients undergoing initial NPAF ablation (median follow-up: 4.0 years). Based on the timing of the final ERAT, we divided the patients into No-ERAT (N = 154, without ERAT), Early (N = 39, 0–7 days after ablation), Intermediate (N = 67, 8–30), and Late-ERAT (N = 70, 31–90) groups. We assessed the extent of LARR, defined as the percentage of decrease in LAV (%ΔLAV). The %ΔLAV cutoff value was determined by receiver operating characteristic analysis, and incorporated into a multivariate analysis to assess the association between ERAT and LARR. Results: Late - ERAT was associated with LR (hazard ratio: 6.31, 95% confidence interval (CI): 4.21–9.47, p = 0.0001). The %ΔLAV in the Late-ERAT group was significantly smaller than the other groups ( p < 0.0001). The predictive power of %ΔLAV for LR was slight (AUC, 0.604; best cutoff, 18.8% decrease; p = 0.0011). In the multivariate logistic regression analysis, Late-ERAT was associated with poor LARR (%ΔLAV < 18.8% decrease) (odds ratio, 0.13; 95%CI, 0.06–0.27; p < 0.001), whereas Early- and Intermediate-ERAT did not show any correlation. Conclusions: Late-ERAT was strongly associated with poor LARR after NPAF ablation. Both Late-ERAT and poor LARR might reflect a residual arrhythmogenic substrate causing LR.